An Economic Analysis of Interest Rate Swaps - BICKSLER, JAMES; CHEN, ANDREW H. (Journal of Finance, 1986)
ABSTRACT Interest rate swaps, a financial innovation in recent years, are based upon the principle of comparative advantage. An interest rate swap is a useful tool for active liability management and for hedging against interest rate risk. The purpose of this paper is to provide a simple economic analysis of interest rate swaps. Alternative uses of and the appropriate valuation procedure for interest rate swaps are described.